Parathyroid adenoma with intraoperative indocyanine green localization: a case report - Chandrasekaran, Varshini; Rajavelu, Narayanan; Padmanabhan, Naveen (International Surgery Journal, 2025)
Intra operative identification of parathyroid glands poses a major difficulty while performing parathyroidectomy or total thyroidectomy, due to the close resemblance with fatty tissues and risk of hypocalcemia. To minimize these complications and to enhance the chances of accurate clinical identification, a number of techniques have been developed and tested along the years. One such novel technique that has been developed is the use of indocyanine green (ICG) and near infrared fluorescence imaging. Per operative ICG fluorescence aids in the accurate identification of the glandular tissue and targeted resection of the same. The following case report is that of a 65-year-old male who was evaluated for hip pain and found to have parathyroid adenoma of the right gland and how intra operative ICG administration aided us in the accurate identification and resection of the gland.